The Causes of Fiscal Transparency: Evidence from the American States - James E. Alt; David Dreyer Lassen; Shanna Rose (University of Copenhagen, Economic Policy Research Unit (EPRU), 2006)
We use unique panel data on the evolution of transparent budget procedures in the American states over the past three decades to explore the political and economic determinants of fiscal transparency. Our case studies and quantitative analysis suggest that both politics and fiscal policy outcomes influence the level of transparency. More equal political competition and power sharing are associated with both greater levels of fiscal transparency and increases in fiscal transparency during the sample period. Political polarization and past fiscal conditions, in particular state government debt and budget imbalance, also appear to affect the level of transparency.
Keywords: D72; D78; H70; 330; Öffentliche Finanzen; Finanzkontrolle; Neue politische Ökonomie; USA; Fiskalische Transparenz; Datenerhebung